A Model for Treating Voice Disorders in School-Age Children within a Video Gaming Environment. - King, Suzanne N.; Davis, Larry; Lehman, Jeffrey J.; Ruddy, Bari Hoffman (Journal of Voice, 2012)
Summary: Objective: Clinicians use a variety of approaches to motivate children with hyperfunctional voice disorders to comply with voice therapy in a therapeutic session and improve the motivation of children to practice home-based exercises. Utilization of current entertainment technology in such approaches may improve participation and motivation in voice therapy. The purpose of this study is to test the feasibility of using an entertainment video game as a therapy device. Study Design: Prospective cohort and case-control study. Methods: Three levels of game testing were conducted to an existing entertainment video game for use as a voice therapy protocol. The game was tested by two computer programmers and five normal participants. The third level of testing was a case study with a child diagnosed with a hyperfunctional voice disorder. Modifications to the game were made after each feasibility test. Results: Errors with the video game performance were modified, including the addition of a time stamp directory and game controller. Resonance voice exercises were modified to accommodate the gaming environment and unique competitive situation, including speech rate, acoustic parameters, game speed, and point allocations. Conclusion: The development of video games for voice therapeutic purposes attempt to replicate the high levels of engagement and motivation attained with entertainment video games, stimulating a more productive means of learning while doing. This case study found that a purely entertainment video game can be implemented as a voice therapeutic protocol based on information obtained from the case study.